A Qualitative Study of Teachers’ Strategies in Strengthening Students’ Listening Ability - Dedek Silfa; Nuzulul Isna (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Listening plays a crucial role in English language learning. However, many students continue to experience difficulties in understanding spoken English, requiring teachers to employ effective instructional strategies. This study aimed to explore the strategies used by English teachers to improve their students' listening skills, the challenges they faced when implementing these strategies, and the factors that support listening instruction in private junior high schools in Southwest Aceh. The study contributes to the limited research on listening instruction in private junior high schools in Southwest Aceh. A qualitative descriptive design was employed using purposive sampling to conducted eight English teachers from six private junior high schools. Data were collected through semi-structured interviews and analysed using Braun and Clarke's (2006) six-phase thematic analysis. The findings generated three overarching themes: (1) listening teaching strategies, consisting of in-class and outside-class practices; (2) challenges encountered by teachers, including student-related, language-related, and technical challenges; and (3) supporting factors, comprising school facilities, teaching materials, and human support. These findings provide practical implications for English teachers by emphasizing the importance of integrating structured classroom instruction with independent listening practice while addressing contextual factors that influence effective listening instruction.